2021
DOI: 10.1007/s12020-021-02743-9
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in BACH2 gene is a marker of polyglandular autoimmunity

Abstract: Purpose Genetically predisposed individuals may develop several autoimmune diseases—autoimmune polyendocrine syndromes (APS). APS types 2–4, are complex disorders, which combine various organ-specific autoimmune conditions. Recent reports support the considerable role of the BACH2 gene in immune cell differentiation and shifting the T-cell balance towards regulatory T-cells. BACH2 polymorphisms are associated with autoimmune disorders, including Addison’s disease (AD), Graves’ disease (GD), and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Most recently, evidence by Fichna et al. appears to show that BTB domain and CNC homolog 2 ( BACH2 ) gene polymorphism, implicated in lymphocyte differentiation and function, may also promote multitarget autoimmunity ( 47 ). Genetic screening is growing popular to identify patients at risk of autoimmune disorders, though this remains too expensive to be included in routine clinical management and is not readily available.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, evidence by Fichna et al. appears to show that BTB domain and CNC homolog 2 ( BACH2 ) gene polymorphism, implicated in lymphocyte differentiation and function, may also promote multitarget autoimmunity ( 47 ). Genetic screening is growing popular to identify patients at risk of autoimmune disorders, though this remains too expensive to be included in routine clinical management and is not readily available.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the identified differentially methylated genes have important roles in T-cell and immune function. As an example, BACH2 is a transcription factor that regulates lymphocyte development [ 86 ], and polymorphisms in BACH2 have been associated with some autoimmune conditions [ 87 ]. It has been reported that BACH2 participates in oxidative stress-mediated apoptosis and is involved in innate immunity and adaptive immune responses [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocyte maturation defects and upper respiratory chest infections have been reported in patients with BACH2 heterozygous mutations (Afzali et al 2017). Recent human genetic studies indicated a genetic polymorphism within the BACH2 gene locus and its association with autoimmune conditions such as autoimmune thyroid disease, Addison's disease, systemic lupus erythematosus among others and diabetes type 1 (Fichna et al 2021). In addition, BACH2 had a signi cant effect in human diabetes type 2 islets by restoring a nondiabetic phenotype (Son et al 2021) and in a gene expression pro ling study of patients with myocardial infarction (Qiu and Liu 2019).…”
Section: Discussionmentioning
confidence: 99%